2018
DOI: 10.1071/sr16356
|View full text |Cite
|
Sign up to set email alerts
|

Ecological niche differentiation of ammonia-oxidising archaea and bacteria in acidic soils due to land use change

Abstract: Nitrification can be driven by either ammonia-oxidising bacteria (AOB) or ammonia-oxidising archaea (AOA) and is a central process in the nitrogen cycle. However, to date, it is not clear how the ecological niche differentiation of AOB and AOA are affected by land use and management changes in strongly acidic soils in subtropical China. In this study, three different land-use acidic soils – forest, upland, and paddy soils – were collected and a DNA Stable-Isotope Probing experiment performed to determine the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…This result accorded with a previous study that found soil temperature was the important driver of global soil nitrification rate (Li et al 2020). Some studies have observed niche differentiation between the AOA and AOB communities across different land use types (Dai et al 2018;Hink et al 2018;Liuet al 2018). The inconsistency between our results and previous hypothesis indicated that land use changes in alkaline soil did not significantly affect the AOA and AOB community diversity (Fig.…”
Section: Factors Indirectly and Directly Regulate Ecosystem Functionssupporting
confidence: 91%
“…This result accorded with a previous study that found soil temperature was the important driver of global soil nitrification rate (Li et al 2020). Some studies have observed niche differentiation between the AOA and AOB communities across different land use types (Dai et al 2018;Hink et al 2018;Liuet al 2018). The inconsistency between our results and previous hypothesis indicated that land use changes in alkaline soil did not significantly affect the AOA and AOB community diversity (Fig.…”
Section: Factors Indirectly and Directly Regulate Ecosystem Functionssupporting
confidence: 91%
“…This result is in accordance with a previous study that found soil temperature was an important driver of the global soil nitrification rate (Li et al., 2020). Some studies have observed niche differentiation between the AOA and AOB communities across different land use types (Dai et al., 2018; Hink et al., 2018; Liu et al., 2018). However, our study cannot directly support the hypothesis of niche differentiation because land use change did not significant affect the AOA and AOB community (Figure 2b,c).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that nitrification activity in acidic soils is positively correlated with AOA abundance (7,10), and changes of AOA communities could significantly affect nitrification activity (7,11,12). However, recent studies of acidic upland soils have found that AOB are associated with potential nitrification rates (13) and act as metabolically active ammonia oxidizers (14)(15)(16). Such evidence could indicate that the assumption of AOA dominating nitrification in acidic soils may not hold true for all soil types and that the role of AOB in nitrification in acidic soils should be reevaluated.…”
mentioning
confidence: 99%